2013
DOI: 10.1186/1471-2164-14-801
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing identification of novel and conserved miRNAs in the Brassica oleracea leaves

Abstract: BackgroundPlant microRNAs are short (~21 nt) non-coding molecules that regulate gene expression by targeting the mRNA cleavage or protein translation inhibition. In this manner, they play many important roles in the cells of living organisms. One of the plant species in which the entire set of miRNAs has not been yet completely identified is Brassica oleracea var. capitata (cabbage). For this reason and for the economic and nutritional importance of this food crop, high-throughput small RNAs sequencing has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 100 publications
4
30
0
Order By: Relevance
“…In this study, two sRNA libraries from radish leaves were constructed during vegetative and reproductive stage and sequenced by NGS sequencing. 21-nt sRNA groups were predominant, which was consistent with the reports on tissue-specific miRNAs in B. oleracea 48 , wild rice 24 and castor bean 49 , implying that 21 nt miRNAs may be canonical miRNAs in plants 8 24 .…”
Section: Discussionsupporting
confidence: 90%
“…In this study, two sRNA libraries from radish leaves were constructed during vegetative and reproductive stage and sequenced by NGS sequencing. 21-nt sRNA groups were predominant, which was consistent with the reports on tissue-specific miRNAs in B. oleracea 48 , wild rice 24 and castor bean 49 , implying that 21 nt miRNAs may be canonical miRNAs in plants 8 24 .…”
Section: Discussionsupporting
confidence: 90%
“…() identified a set of miRNA candidates or variant sequences in the B. napus genome and Lukasik et al . () and Wang et al . () reported a new set of miRNAs of B. oleracea , from which 206 conserved and 60 novel miRNAs are included in our sets.…”
Section: Discussionmentioning
confidence: 91%
“…A broad variation in miRNA expression was observed. Some of the conserved miRNAs, such as miR156, miR166, miR167 and miR172, were found to be the most abundant, which is in agreement with previous findings (Lukasik et al ., ; Yanik et al ., ). In our study, miR535 has been identified as one of the most up‐regulated miRNAs (Table ), similarly as reported by others (Xia et al ., ).…”
Section: Discussionmentioning
confidence: 99%